Impact of income and social deprivation on meat consumption in Mexico: Consumo de carne en México y carencias sociales. - Huerta-Sanabria, Sandy; Arana-Coronado, Óscar Antonio; Sagarnaga Villegas, Leticia Myriam; Matus-Gardea, Jaime Arturo; Brambila Paz, Jose de Jesus (Revista Mexicana de Ciencias Agrícolas, 2018)
The consumption of meat is important for the human being, due to the protein benefits of high biological value that this food contains. In addition to income there are other variables such as social deprivation, which also determine the consumption of meat. Identifying meat consumers in economic groups will help to understand the relationship between income and social deprivation with the consumption of this good. In July of 2014, an exploratory survey was conducted with a sample of 429 Mexican families the data are of a mixed nature, supported by a questionnaire of 43 questions, of which 20 were designed under the methodology of multidimensional measurement of poverty of the CONEVAL, in order to detect the index of social deprivation of the consumers surveyed. An F test was applied to check homogeneity of variances in the weekly consumption of meat of the three economic groups detected (vulnerable due to social deprivation, moderate multidimensional poor and extreme multidimensional poor). Finally, the Student’s T test was carried out to check whether there is a difference in meat consumption between the three economic groups. The results showed that there is indeed a difference in consumption for beef, pork and chicken between the vulnerable group due to social deprivation and extreme multidimensional poverty with a t of 2.8254, 2.686 and 2.2367 respectively. Therefore, it is concluded that, in effect, social deprivation and income directly influence the weekly consumption of meat.